Pengaruh BI Rate dan BOPO terhadap NPL pada Bank Umum yang Terdaftar di BEI Tahun 2010-2020 - Amalia Nur Azizzah; Iwan Setiawan; Kristianingsih Kristianingsih (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The ascent and fall of the NPL ratio in the banking world can be brought about a few components, both inward and outside to the bank, just as elements from the indebted person inself. This last task research means to decide the impact of the BI Rate and BOPO on NPLs in business banks recorded on the Indonesian Stock Exchange from 2010 to 2020 with an example of fiscal reports from the Q1 of 2010 to the Q4 of 2020 for 6 banking companies. The strategy utilized in this examination is a quantitative exploration technique with the assistance of board information relapse testing. The chose board information relapse technique is the Random Effect Model, whit the outcome that the BI Rate has a hug impact a negative way and BOPO has a critical impact a positive way NPL